The Concept of Zero Waste in the Context of Supporting Environmental Protection by Consumers - Bogusz, Małgorzata; Matysik-Pejas, Renata; Krasnodębski, Andrzej; Dziekański, Paweł (Energies (Basel), 2021)
Zero waste according to the Zero Waste International Alliance is an ethical, economical, effective and forward-thinking concept whereby people can change their lifestyles and habits to one that mimics natural cycles, where all discarded materials are designed to become resources that can benefit others. The aim of the study was to determine the knowledge of the Zero Waste problem (subject of the study) by respondents in selected Central and Eastern European countries, including Poland, Slovakia (EU countries) and Ukraine (EU associated country), as well as to verify whether the Zero Waste rules are known and implemented in sustainable activities of residents in the studied countries. The research was carried out using the CAWI method. The research tool was a structured questionnaire. The analysis of data from the countries covered by the study showed a significant relationship between the basic elements in the daily functioning of households related to the protection of the environment through responsible consumption, reuse and recovery of selected products, packaging and materials and food and the concept of Zero Waste. Research has shown that respondents consciously identify these activities with Zero Waste. According to the authors, the results of the research are the basis for public discussion at the European and global level in the field of creating legal regulations and educational programs in the context of waste management.